Online Diary System / Tham Kok Keen - Tham, Kok Keen (2004)
This project documentation is a submitted to the Faculty of Computer Science and Information Technology. University of Malaya as a report for the final year project which in turn serves as a partial fulfillment of the requirement for the Bachelor of Information Technology Degree. Online Diary System is a web-based application that will change the traditional way of writing diary which is using papers and pens. With this system, users can enjoy writing their diary as long as they have an internet connection. It is also built for the reason of security where only the users can access their own diary. There is no way that one can view the private diary written unless he or she is given permission by the diarist. With the studies made on existing systems, comparison has been made to evaluate each of them on their features and other aspects such as user friendliness, navigation and functions provided. It is found that a diary system is not only an ordinary diary for writing down every sweet and sour moments but there are also some functions that can be added to ease users. Proposed system will include a reminder with SMS alert and address book too. This project is continued with the next advancement of the final year project WXES3183. The actual WXES3182 is based on the proposal in WXES3182, the first stage of the final year project.